MEMILIH KANAL CITRA SENTINEL 2 TERBAIK UNTUK DETEKSI INTRUSI AIR LAUT DI KELURAHAN WAY URANG - Aulia, Mila; Ghazali, Mochamad Firman; Dermawan, Ananda; Salsabila, Choirunnisa; Zahra, Lauditta; Suastini, Ni Made Mega Melliana (J SIG (Jurnal Sains Informasi Geografi), 2023)
The phenomenon of sea water intrusion almost occurs in all coastal areas. This phenomenon occurs scientifically and non-scientific which can lead to reduced groundwater quality. Utilization of remote sensing images, such as Sentinel 2 can be used to map the distribution of seawater intrusion in Way Urang Urban Village, South Lampung Regency. It just needs to be preceded by choosing the right band. Therefore, the statistical test process in the form of regression needs to be considered. The data needed include seawater intrusion in the field in the form of 18 sample points and Sentinel 2 Satellite Imagery. Based on the results of the regression test, bands 9, 10, 11, and 12 are bad bands with an R2 value of 0.0032-0.0624, bands 1, 6, 7, 8, 8A with an average value of R2 0.1171-0.0624 is a poor band, and bands 2, 3, 4, especially band 5 with R2 0.2099-0.3483 are the best bands in mapping the distribution of seawater intrusion. However, the Root Mean Square Error (RMSE) value of band 8A is 0.2570 which is smaller than band 5 which is 0.4335. So it can be said that band 5 is the best in mapping seawater intrusion with the highest R2 value. But if we look at the RMSE value, band 8A has better accuracy than band 5.